In Vivo Antimicrobial Activity Of Indian Medicinal Plant Tinospora Cordifolia Using Serial Tube Dilution Technique - Sharma, Abhimanyu; Batra, A (Asian Journal of Pharmaceutical Research and Development, 2013)
The present study designed for the methanolic extracts of different in vivo (root, stem, leaf and bark) plant samples of Tinospora cardifolia (family: Menispermaceae) were screened for their antimicrobial activity against Escherichia coli, E. cloacae, Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa, A. niger, A. flavus, A. solani, R. stolonifer and F. oxisporum by using the MIC “Serial tube dilution technique” and agar well diffusion method. It is clear from the results that, the extracts of these plants acts as a good source of antibiotics against various bacterial and fungal pathogens tested and exhibited broad spectrum of antimicrobial activity. The largest zone of inhibition was observed for methanolic leaf extract against Staphylococcus aureus (15.5 ± 0.14 mm) and minimum was observed in bark against F. oxisporum and Pseudomonas aeruginosa (6.0 ± 0.45mm). Minimum inhibitory concentration (MIC) may be defined, as the lowest concentration of antimicrobial agent requires to inhibit the growth of organism. The maximum MIC values were recorded in stem and leaf i.e 128 µg/ml against Bacillus cereus, Staphylococcus aureus, A. niger, A. flavus, A. solani and R. stolonifer.The study suggest further research regarding the pharmacological investigations of this plant and also support the continued sustainable use of these plants in traditional systems of medicine.